Microcentralidades urbanas: diseño de un equipamiento comercial en el sector de Yuyucocha-Ibarra - Castro Rocha, Nathaly Mishell (2023)
In Ibarra since the beginnings of the 2000’s the urban expansion was an imminent solution through the human settlement. During the organic development the Yuyucocha sector is placed in a residential area with an easy access, nevertheless is displaced to the periphery or rural-urban zone because of it own intern distribution, where the estates of the sector, all along it exists few open places and even residual ones which make difficult the mobility inside it and generates an edge with the close areas rural- urban of the city The spaces inside of the city marks a clear distance but no for the limitation but by the proximity and the congruence of the activities inside it own. It can’t meet with the wished expectations that can afford the comfort way of living. This situation generates a nonconformity of the community so has been raised different equipment for the users as the municipal kitchen or the Water Park although every single project has been declined or not concluded. The sector has been collapsed by a residential use that generates segregation of the spaces directing it to a single land use.